New approaches to evaluating complex health and care systems. (1st February 2016) - Lamont, Tara; Barber, Nicholas; Pury, John de; Fulop, Naomi; Garfield-Birkbeck, Stephanie; Lilford, Richard; Mear, Liz; Raine, Rosalind; Fitzpatrick, Ray
Abstract : Tara Lamont and colleagues discuss how researchers can help service leaders to evaluate rapidly changing models of care, with a range of approaches depending on needs and resources